1973
DOI: 10.1084/jem.137.5.1226
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Induced Diabetes Mellitus

Abstract: Infection of DBA/2N male mice with encephalomyocarditis virus resulted in a diabeteslike syndrome characterized by hyperglycemia, glycosuria, hypoinsulinemia, polydipsia, and polyphagia. Blood glucose levels were elevated within 4 days after infection and reached a maximum mean level of 320 mg/100 ml within 12 days. Approximately 60–80% of the animals developed a transient hyperglycemia while 10–15% of the animals remained hyperglycemic for well over 6 mo. The remaining animals failed to become hyperglycemic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
2

Year Published

1976
1976
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(16 citation statements)
references
References 11 publications
0
14
2
Order By: Relevance
“…In this connection, it should be emphasized that EMC virus is pantropic; it replicates in many organs, and death is usually due to myocarditis or encephalitis (18,19). Lethality varies considerably among EMC-infected inbred strains of mice, but there does not appear to be any direct relationship between lethality and beta cell damage (4,8,19). The possibility that susceptibility of different organ systems to EMC infection may be under the control of different genes merits exploration.…”
Section: Discussionmentioning
confidence: 99%
“…In this connection, it should be emphasized that EMC virus is pantropic; it replicates in many organs, and death is usually due to myocarditis or encephalitis (18,19). Lethality varies considerably among EMC-infected inbred strains of mice, but there does not appear to be any direct relationship between lethality and beta cell damage (4,8,19). The possibility that susceptibility of different organ systems to EMC infection may be under the control of different genes merits exploration.…”
Section: Discussionmentioning
confidence: 99%
“…A diabetes mellitus-like syndrome has been reported in genetically susceptible mice inoculated with either the M variant of encephalomyocarditis (EMC) virus (1,2) or a diabetogenic variant of coxsackie B4 virus (3). In both of these systems, a rapid lysis of beta cells occurs with the severity of hyperglycemia closely correlating with the degree of virus-induced beta cell destruction (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…In humans there is evidence that viral pancreatitis can be the cause of some cases of diabetes (Levy & Notkins, 1971); in laboratory animals certain types of diabetes can be experimentally induced by viral challenge (Boucher & Notkins, 1973;Yoon etal., 1982). However, tissue culture studies and viral antibody testing have indicated that a viral aetiology is unlikely for MM diabetes (Taylor, 1983).…”
Section: Discussionmentioning
confidence: 99%